Disciplinary power and the process of training informal carers on stroke units. Issue 1 (26th October 2017) - Sadler, Euan; Hawkins, Rebecca; Clarke, David J; Godfrey, Mary; Dickerson, Josie; McKevitt, Christopher
Abstract: This article examines the process of training informal carers on stroke units using the lens of power. Care is usually assumed as a kinship obligation but the state has long had an interest in framing the carer and caring work. Training carers in healthcare settings raises questions about the power of the state and healthcare professionals as its agents to shape expectations and practices related to the caring role. Drawing on Foucault's notion of disciplinary power, we show how disciplinary forms of power exercised in interactions between healthcare professionals and carers shape the engagement and resistance of carers in the process of training. Interview and observational field note extracts are drawn from a multi‐sited study of a training programme on stroke units targeting family carers of people with stroke to consider the consequences of subjecting caring to this intervention. We found that the process of training informal carers on stroke units was not simply a matter of transferring skills from professional to lay person, but entailed disciplinary forms of power intended to shape the conduct of the carer. We interrogate the extent to which a specific kind of carer is produced through such an approach, and the wider implications for the participation of carers in training in healthcare settings and the empowerment of carers.